Case Study of Using the Blending Radar-Numerical Weather Prediction Product in Nowcasting - Van Khiem, Mai; Wang-chun, Woo; Wai-kin, Wong; Siu Lun, Yeung; Duc Tien, Du; Khanh Hung, Mai; Dinh Quan, Dang; Thi Phuong Dung, Pham; Thi Nga, Nguyen; Thi Huyen Trang, Chu (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 3DO - 10.25073/2588-1094/vnuees.4686, 2021)
In the very short-range forecast (less than 12 hours) of heavy rain and severe thunderstorms, the main challenge is primarily on tracking and predictingng of growth and decay of significant convective systems. With the advances in nowcasting techniques, analysis and nowcasting of heavy rain and thunderstorm from radars and satellites have been improving progressively. The intensity changes of convective weather from direct output of numerical weather prediction (NWP) models would contain substantial errors due to data assimilation and spin-up issues of model physical processes. In this paper, we would introduce a new blending system being implemented in NCHMF to enhance nowcasting and forecasting services. The system includes: i) extrapolations of rain/convective systems of Vietnam’s radar mosaic (or single radars) for first 1-6 hours based on radar based on the Short-range Warning of Intense Rainstorms in Localized Systems (SWIRLS) developed by the Hong Kong Observatory (HKO), and ii) a rapidly update convective-permitting NWP system based on WRF-ARW in the convective scale to provide the forecast up to the next 12 hours. Firstly, 1-6 hours forecast from models are calibrated with radar-based quantitative precipitation estimates and nowcasts. The study will present some initial results of the blending system and discuss verification of the quantitative precipitation forecast.